Women influence on the practical role of public relations in Iskandar Malaysia region - Abdul Rahim, Shahrul Amir; Markom, Mohd Nasir; AlSagoff, Syed Agil (Human Resource Management Academic Research Society, 2021)
The role of Public Relations (PR) practitioners is often associated with the extent to which a person is able to carry out his/her responsibilities effectively. Previous studies have often linked the field of PR stereotypically to a career of women rather than men (Niel, 2016; Place, 2015). Public seldom give a negative perception towards the role of women's PR. Therefore, the aim of this study is to find out recent development of the role of women's PR, especially in Iskandar Malaysia. The effort is to learn the real phenomenon of women carries out their duties as PR practitioner. This qualitative study will further explore the issue by phenomenological approach using in-depth interviews among PR practitioners in Iskandar Malaysia. The results of the study has discovered that the importance of the attitude of women’s PR is very important in implementing their relationship with society. They were found remains tightly knotted to their role as technicians rather than managers although without gender competitions. This study is expected to contribute to future improvements in the field of public relations (PR).